2001
DOI: 10.3354/meps221039
|View full text |Cite
|
Sign up to set email alerts
|

Microbial population dynamics and diversity during a bloom of the marine coccolithophorid Emiliania huxleyi (Haptophyta)

Abstract: Several previous studies have shown that Emiliania huxleyi blooms and terminations have been succeeded by an increase in large virus-like particles (LVLP), strongly suggesting the bloom collapse was caused by viral lysis. However, due to methodological limitations, knowledge of how such blooms affect the rest of the microbial community is limited. In the current study we induced a bloom of E. huxleyi in seawater enclosures and applied methods enabling us to describe the algae, bacteria and virus communities wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(118 citation statements)
references
References 22 publications
8
104
1
5
Order By: Relevance
“…It had switched from E. huxleyi domination (Station 1) to a mixture of autotrophic dino£agellates (550 mm), nanophytoplankton, cryptophytes and picoeukaryotes, whose concentrations were all higher inside the high re£ectance area suggesting that virus-induced E. huxleyi lysis had triggered a rapid succession of the phytoplankton community. Castberg et al (2001) reached a similar conclusion using Isolation of viruses responsible for the demise of an Emiliania huxleyi bloom W.H. Wilson et al 375 molecular methods (denaturing gradient gel electrophoresis) where they demonstrated that a new eukaryote community developed following the virus-induced demise of an E. huxleyi bloom during a seawater mesocosm experiment.…”
Section: Transect Datamentioning
confidence: 80%
See 2 more Smart Citations
“…It had switched from E. huxleyi domination (Station 1) to a mixture of autotrophic dino£agellates (550 mm), nanophytoplankton, cryptophytes and picoeukaryotes, whose concentrations were all higher inside the high re£ectance area suggesting that virus-induced E. huxleyi lysis had triggered a rapid succession of the phytoplankton community. Castberg et al (2001) reached a similar conclusion using Isolation of viruses responsible for the demise of an Emiliania huxleyi bloom W.H. Wilson et al 375 molecular methods (denaturing gradient gel electrophoresis) where they demonstrated that a new eukaryote community developed following the virus-induced demise of an E. huxleyi bloom during a seawater mesocosm experiment.…”
Section: Transect Datamentioning
confidence: 80%
“…Although such conclusions from similar data sets are not new (Bratbak et al, 1993Brussaard et al, 1996;Castberg et al, 2001), there have been no reports of E. huxleyi-speci¢c viruses being isolated and maintained in culture from E. huxleyi blooms. Bratbak et al (1996) reported the initial isolation of a virus by plaque assay, however they were unable to propagate it further for characterization.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have investigated the role of viruses in controlling the bloom development of E. huxleyi (Bratbak et al, 1993, Brussaard et al, 1996, Castberg et al, 2001, Jaquet et al, 2002, Wilson et al, 1998, 2002a, 2002b. It became evident from these investigations that viruses are intrinsically linked to the decline of E. huxleyi blooms.…”
Section: Introductionmentioning
confidence: 99%
“…During the stationary phase, the cells are generally covered by several layers of coccoliths and the distal ones are released into the water column when new ones are produced (Paasche, 2002). This phase is often associated with the decay of the bloom, when high abundance of E. huxleyi coincides with those of viruses, enhancing viral infection and bloom termination (Catsberg et al, 2001;Jacquet et al, 2002). The persistence of coccolithophorid blooms after nutrient exhaustion is haphazard and patchy in natural environments.…”
Section: Introductionmentioning
confidence: 99%